Generating and Allocating Internal Revenue for Public Secondary School Administration in Cross River State - Nyeh, Comfort Omori; Kpee, G. G. (Advances in Social Sciences Research Journal, 2019)
The design adopted for this study was correlation. Population of the study consisted of all the 504 public secondary schools principals in 18 LGAs in Cross Rivers State. However, purposive sampling technique was use to select the 504 principals a sample for the study. There were two research questions and two hypotheses formulated for the study. Questionnaire was the instrument used for data collection with 20 items and titled “Generation and Allocation of Internal Revenue for School Administration Questionnaire” (GAIRSAQ). The GAIRSAQ was validated by the researchers’ supervisors as well as two experts from Measurement and Evaluation in the Department of Psychology, Guidance and Counseling. Split half statistic associated with Spearman Brown prophecy formula was used to estimate the reliability of the questionnaire with co-efficient of 0.86. Mean, standard deviation and rank order were used to answer the research questions while z-test was used to test the hypotheses at 0.05 level of significance. The findings of the study showed that rentage, community assistance, PTA contributions, fund raising campaigns were among the strategies for generating revenue in public secondary schools in Cross River State. The study also showed that revenue was majorly allocated based on the urgency of the need and that revenues generated were utilized for different administrative needs such as provision of facilities, maintenance and day-to-day running of the school. Therefore, it was recommended among others that principals should develop an equitable revenue allocation formula for effective administration of public secondary schools in Cross River State.